2020
DOI: 10.3390/ph13120485
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Anti-Cancer Mechanism of Novel 3,4′-Substituted Diaryl Guanidinium Derivatives

Abstract: We previously identified a guanidinium-based lead compound that inhibited BRAF through a hypothetic type-III allosteric mechanism. Considering the pharmacophore identified in this lead compound (i.e., “lipophilic group”, “di-substituted guanidine”, “phenylguanidine polar end”), several modifications were investigated to improve its cytotoxicity in different cancer cell lines. Thus, several lipophilic groups were explored, the di-substituted guanidine was replaced by a secondary amine and the phenyl ring in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Therefore, there is a need for novel agents targeting key oncogenic signaling pathways. VP79s derives from a class of 3,4 ′ -bis-guanidinium pyridinophenyl ether compounds which we have previously shown to exhibit anti-cancer activity against a number of leukaemia and solid tumour cell lines [12][13][14]. Some of these compounds inhibit BRAF activity through a hypothetical type-III allosteric mechanism, although VP79s appears to induce cytotoxicity independent of Ras/BRAF inhibition in promyelocytic leukaemia cells [14].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, there is a need for novel agents targeting key oncogenic signaling pathways. VP79s derives from a class of 3,4 ′ -bis-guanidinium pyridinophenyl ether compounds which we have previously shown to exhibit anti-cancer activity against a number of leukaemia and solid tumour cell lines [12][13][14]. Some of these compounds inhibit BRAF activity through a hypothetical type-III allosteric mechanism, although VP79s appears to induce cytotoxicity independent of Ras/BRAF inhibition in promyelocytic leukaemia cells [14].…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that VP79s does not inhibit downstream BRAF signaling in promyelocytic leukaemia cells, unlike related compounds which exhibit type III allosteric inhibition of BRAF [14]. Here, we investigated the effect of VP79s on the activation of ERK, a MAP kinase which lies downstream of BRAF, in MM cells.…”
Section: Vp79s Activates Mitogen-activated Protein (Map) Kinase Signa...mentioning
confidence: 99%
See 3 more Smart Citations